95.1k views
1 vote
Write a equation for the polynomail graphed below

Write a equation for the polynomail graphed below-example-1
User Joe Taras
by
5.4k points

1 Answer

4 votes

Answer:

y(x) = (1/9)(x +4)(x +3)(x -1)(x -3)

Explanation:

It has roots at -4, -3, 1, and 3 so can be written in the form ...

y(x) = a(x +4)(x +3)(x -1)(x -3)

We can determine at the value of "a" by looking at the y-intercept. Filling in x=0 in the above equation, we get ...

y(0) = 36a

We see on the graph that y(0) = 4, so "a" is ...

4 = 36a

4/36 = 1/9 = a

The polynomial is ...

y(x) = (1/9)(x +4)(x +3)(x -1)(x -3)

Write a equation for the polynomail graphed below-example-1
User Rakesh N
by
6.1k points